Sugarcane juice for human health and opportunities of employment generation - Mahata, Goutam (Indian Farming, 2019)
Sugarcane juice, a magic juice, is good for human health. People consume it as an energy drink without knowing the diversified health benefits. Proper awareness and frequent publication regarding benefits of sugarcane juice at Government level through different media is essential for maintaining good health of the people. Diabetic patients can also consume sugarcane juice because of low glycemic index (GI). Demands of sugarcane juice can easily be seen by the huge crowd rounding the roadside vendors, waiting a glass of sugarcane juice. Installation of sugarcane juice bars/ outlets/stalls within the Airports, Railway Stations, Bus Stands, Hospital campuses, Shopping Malls, Market complexes, educational institutes, different government offices, IT Parks, Kishan Mandies, Parks, Tourist Spots, Religious places, etc. by Government/Private companies/P-P-P model/Cooperatives/ Individual farmers can drastically change the scenario and having huge opportunities of employment generation as well as increase the income of the sugarcane growers in India.